Generalized power law model of blood flow in a stenosed bifurcated artery - Muhammad Sabaruddin Ahmad Jamali; Zuhaila Ismail (Research and Social Study Institute, 2019)
Stenosis is a blockage caused by atherosclerosis literally lead to serious circulatory complaints, by narrowing the vessel wall and causing an alternation in the flow structure which consequently reduced the fluid flow passing to the other organs and tissues. This study, the geometry of the bifurcated is considered with presence of stenosis at mother and daughter artery. The blood vessel is modelled as a two-dimensional (2D) rigid wall since the wall of a disease artery is reported to be less compliant. The blood will be assumed as incompressible, laminar, steady and characterized as the generalized power-law model. Simulation result is obtained by using COMSOL Multiphysics 5.2, a software based on the FEM to solve the problem. Results concerning the effect of different blood rheology and severity of stenosis on the streamlines pattern are discussed.